2016
DOI: 10.18632/oncotarget.9287
|View full text |Cite
|
Sign up to set email alerts
|

Mouse double minute 2 (MDM2) upregulates Snail expression and induces epithelial-to-mesenchymal transition in breast cancer cells in vitro and in vivo

Abstract: The oncogene, mouse double minute 2 (MDM2), has been implicated in the pathogenesis of numerous cancers. In this study, we investigated the role of MDM2 in epithelial-to-mesenchymal transition (EMT) and the underlying mechanisms in breast cancer cells in vitro and in vivo. The results showed that up-regulation of MDM2 in MCF-7 cells altered the cell morphology to a mesenchymal phenotype. Knockdown of MDM2 in MDA-MB-231 cells altered the cell morphology to the epithelial phenotype. In addition, overexpression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 30 publications
1
21
0
1
Order By: Relevance
“…Moreover, activation of MDM2 elevated the level of Snail, which is critical in cell invasion. Activation of MDM2 was reported to increase Snail level [28]; in consistent with that, inhibition of MDM2 by siRNA signi cantly down-regulated Snail, resulting in decrease of cell invasion. Thus, these data suggests that BC040587/MDM2/Snail is crucial in the cell invasion in response to acidosis.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, activation of MDM2 elevated the level of Snail, which is critical in cell invasion. Activation of MDM2 was reported to increase Snail level [28]; in consistent with that, inhibition of MDM2 by siRNA signi cantly down-regulated Snail, resulting in decrease of cell invasion. Thus, these data suggests that BC040587/MDM2/Snail is crucial in the cell invasion in response to acidosis.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, in our previous study, we found that a potent and selective small molecular MDM2 antagonist Nutlin3 inhibited TGF- β 1-induced EMT in ovarian cancer cells ( Wu et al , 2014b ), indicating the correlation of MDM2 and EMT in ovarian cancer. A recent study demonstrated that MDM2 induced EMT by enhancing Snail expression ( Lu et al , 2016 ); however, whether MDM2 is involved in the TGF- β -Smad signalling pathway thus promoting the progression of EMT remains unclear.…”
mentioning
confidence: 99%
“…In addition, the snail family of zinc-finger transcription factors (snail, slug, and smuc) have been identified as key EMT regulators, and are the ‘master switches’ critical for cell reprogramming8. Recent studies have shown that snail is a key transcription factor involved in the development of EMT, which could repress the expression of E-cadherin by direct binding to the E-box on its promoter, thereby promoting the progression of EMT910.…”
mentioning
confidence: 99%